(untitled) (Eurasian Scientific Herald, 2022)
The article deals with professionally oriented teaching of speech activity based on interdisciplinary integration as a means of forming the professional and communicative competence of non-philologist students in the English language course. The competencybased approach involves the formation of key competencies, one of which is communicative competence, which should be improved in students of all specialties and in the study of all disciplines